Analysis of Heavy Metal Cadmium (Cd) and Lead (Pb) in Eggplant (Solanum melongena L.) in Pontianak City by Using Atomic Absorption Spectrophotometry (AAS) - Nugraha, Fajar; Oktaviani, Syila Malinda; Luliana, Sri (Biology, Medicine, & Natural Product Chemistry, 2024)
In Indonesia, eggplant is a favored vegetable with substantial production. The main objective of this study is to investigate the level of safety of eggplants marketed in traditional wholesale markets in Pontianak City against possible contamination of the heavy metals cadmium (Cd) and lead (Pb), which are commonly discovered in water waste, vehicle exhaust, and excessive pesticide and fertilizer use. Alizarin Red S for Cd metal and Dithizon for Pb metal were used in qualitative assays. Cd and Pb levels were measures using an Atomic Absorption Spechtrophotometer (AAS) instrument. The analytical method has been verified for linearity, accuracy, precision, limit of detection, and limit of quantification. The qualitative test results showed that all samples had positive results for Cd and Pb. The quantitative test results revealed that the Cd and Pb metal contents in the FB (Flamboyan) sample were 0.056 mg/kg and 3.5066 mg/kg, consequently, while they were 0.0986 mg/kg and 3.957 mg/kg, consequently, in the PR (Puring) sample. In keeping with BPOM standard No. 5 of 2018, Cd metal levels in FB samples are at a safe threshold, while Cd metal levels in PR samples and Pb metal levels in FB and PR samples exceed the maximum thresholds that have been set.